Elucidating the role of Ti3AlC2 in low carbon MgO-C refractories: Antioxidant or alternative carbon source?. Issue 9 (August 2018) - Chen, Junfeng; Li, Nan; Hubálková, Jana; Aneziris, C.G.
Abstract: Different approaches to develop low-carbon refractories have been recently proposed. Among them, the use of Ti3 AlC2 can influence the corroded interface and improve the corrosion resistance of low-carbon containing refractories, but current understanding of the role of Ti3 AlC2 is far from complete. In this work, the impact of the single additives Ti3 AlC2 and Si as well as their combination on the microstructure and properties of MgO-C refractories were evaluated. The newly formed ceramic bonding phases contribute to superior mechanical properties. However, the high volume expansion of Ti3 AlC2 led to adverse effect when using Ti3 AlC2 as single antioxidant. The combination of Ti3 AlC2 and Si could inhibit the rapid oxidation and excessive expansion of Ti3 AlC2 .